Promoting biodiversity in food systems - Hawkins, Irana W. (Boca Raton, FL : CRC Press, Taylor & Francis, 2018)
Biodiversity of the food system is crucial for food production and loss of biodiversity is a pressing issue. This book focuses on biodiversity's crucial role in food systems, health and well-being, and fate of the natural environment. It provides practical recommendations on how proper food systems can sustain a healthier planet and protect biodiversity. Sections provide a comprehensive understanding of the urgent need for promoting biodiversity-promoting food systems that help maintain planetary boundaries that are at risk; mimic the natural processes of highly integrated ecosystems; and improve human/planetary health while providing a wholesome and sufficient food supply.
OCLC-licensed vendor bibliographic record.
Keywords: Agrobiodiversity; Food industry and trade -- Environmental aspects; Food security; Nutrition; Functional foods; Lifestyles -- Health aspects; BUSINESS & ECONOMICS / Real Estate / General; MEDICAL / Nutrition; MEDICAL / Public Health; TECHNOLOGY / Agriculture / Forestry